Comparison of simulated parallel transmit body arrays at 3 T using excitation uniformity, global SAR, local SAR, and power efficiency metrics. Issue 3 (18th April 2014) - Guérin, Bastien; Gebhardt, Matthias; Serano, Peter; Adalsteinsson, Elfar; Hamm, Michael; Pfeuffer, Josef; Nistler, Juergen; Wald, Lawrence L.
<x xml:space="preserve">Abstract</x> Purpose We compare the performance of eight parallel transmit (pTx) body arrays with up to 32 channels and a standard birdcage design. Excitation uniformity, local specific absorption rate (SAR), global SAR, and power metrics are analyzed in the torso at 3 T for radiofrequency (RF)‐shimming and 2‐spoke excitations. Methods We used a fast cosimulation strategy for field calculation in the presence of coupling between transmit channels. We designed spoke pulses using magnitude least squares optimization with explicit constraint of SAR and power and compared the performance of the different pTx coils using the L‐curve method. Results PTx arrays outperformed the conventional birdcage coil in all metrics except peak and average power efficiency. The presence of coupling exacerbated this power efficiency problem. At constant excitation fidelity, the pTx array with 24 channels arranged in three z‐rows could decrease local SAR more than 4‐fold (2‐fold) for RF‐shimming (2‐spoke) compared to the birdcage coil for pulses of equal duration. Multi‐row pTx coils had a marked performance advantage compared to single row designs, especially for coronal imaging. Conclusion PTx coils can simultaneously improve the excitation uniformity and reduce SAR compared to a birdcage coil when SAR metrics are explicitly constrained in the pulse design. Magn Reson Med 73:1137–1150, 2015. © 2014 Wiley Periodicals, Inc.